2018
DOI: 10.3390/ijms19103137
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of DNA Damage in the Pathogenesis of the C9orf72 Repeat Expansion in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal, rapidly progressing neurodegenerative disease affecting motor neurons, and frontotemporal dementia (FTD) is a behavioural disorder resulting in early-onset dementia. Hexanucleotide (G4C2) repeat expansions in the gene encoding chromosome 9 open reading frame 72 (C9orf72) are the major cause of familial forms of both ALS (~40%) and FTD (~20%) worldwide. The C9orf72 repeat expansion is known to form abnormal nuclei acid structures, such as hairpins, G-quadruplexes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 178 publications
(220 reference statements)
0
22
0
Order By: Relevance
“…While many of these processes have already been implicated in C9ALS/FTD, there is increasing interest in the role of genomic instability resulting from genotoxic DNA DSBs and/or reduced DNA DSB repair efficiencies as a common feature of neurodegenerative diseases [36,37,39,74,75]. Increased DNA DSB frequency with a concomitant activation of response and repair machinery has been observed in C9ALS/FTD clinical tissues, iPSC motor neurons, and cells expressing synthetic DPRs [52,71,72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many of these processes have already been implicated in C9ALS/FTD, there is increasing interest in the role of genomic instability resulting from genotoxic DNA DSBs and/or reduced DNA DSB repair efficiencies as a common feature of neurodegenerative diseases [36,37,39,74,75]. Increased DNA DSB frequency with a concomitant activation of response and repair machinery has been observed in C9ALS/FTD clinical tissues, iPSC motor neurons, and cells expressing synthetic DPRs [52,71,72].…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of DNA DSBs is increasingly recognized as an emerging feature of C9ALS/FTD and also other neurodegenerative diseases [36,37], potentially due to the unique pressure that neurons are under to maintain genomic stability [38,39]. As a consequence of their inability to utilize homologous recombination (the preferred DNA DSB repair pathway utilized by most replicating cells), high oxygen consumption, high transcription rates and longevity, neurons must utilize elaborate DNA damage response and repair cascades to maintain genomic integrity [36]. Pathways utilized by neurons to repair DNA DSBs include non-homologous end joining (NHEJ) and homology-directed repair pathways; the latter being particularly relevant for the repair of actively transcribed DNA [40][41][42][43]..…”
Section: Introductionmentioning
confidence: 99%
“…Genetic and cell-based studies of human SETX, together with biochemical characterization of its yeast ortholog Sen1, have suggested that SETX protects genomic stability via resolution of R-loops, assisting replication fork progression across transcribing genomic regions and promoting HR at DSBs. In the light of recent findings on implication of genomic instability in neurodegenerative diseases, as reviewed in [115][116][117][118], in-depth studies are required to precisely delineate role of SETX in ALS4. Thus, it is apposite to test if ALS4 gain-of-function mutations affect SETX activities pertaining to DSB repair.…”
Section: Resultsmentioning
confidence: 99%
“…The DNA damage is thought to be a widespread initiator of neuronal apoptosis, and accumulation of damaged DNA has been found in pathological brains, such as in neurodegenerative diseases [5,30,74]. P53 and its downstream signaling pathways are activated in response to DNA damage and play critical roles in DNA damage-induced apoptosis in neurons [37,75,76].…”
Section: Discussionmentioning
confidence: 99%